Stabilization of proteins embedded in sugars and water as studied by dielectric spectroscopy. Issue 37 (15th September 2020) - Olsson, Christoffer; Zangana, Rano; Swenson, Jan
Abstract : Illustration of how a relatively large amount of disaccharides stabilizes proteins (left figure) more than a very low concentration (right figure). Abstract : In many products proteins have become an important component, and the long-term properties of these products are directly dependent on the stability of their proteins. To enhance this stability it has become common to add disaccharides in general, and trehalose in particular. However, the mechanisms by which disaccharides stabilize proteins and other biological materials are still not fully understood, and therefore we have here used broadband dielectric spectroscopy to investigate the stabilizing effect of the disaccharides trehalose and sucrose on myoglobin, with the aim to enhance this understanding in general and to obtain specific insights into why trehalose exhibits extraordinary stabilizing properties. The results show the existence of three or four clearly observed relaxation processes, where the three common relaxations are the local (β) water relaxation below the glass transition temperature ( T g ), the structural α -relaxation of the solvent, observed above T g, and an even slower protein relaxation due to large-scale conformational protein motions. For the trehalose containing samples with less than 50 wt% myoglobin a fourth relaxation process was observed due to a β-relaxation of trehalose below T g . This latter process, which was assigned to intramolecular rotations of the monosaccharide rings in trehalose, could not be detected for high protein concentrations or for the sucrose containing samples. Since sucrose has previously been found to form more intramolecular hydrogen bonds at the present hydration levels, it is likely that this rotation becomes too slow to be observed in the case of sucrose. However, this sugar relaxation has probably less influence on the protein stability below T g, where the better stabilizing effect of trehalose on proteins can be explained by our observation that trehalose slows down the water relaxation more than sucrose does. Finally, we show that the α-relaxation of the solvent and the large-scale protein motions exhibit similar temperature dependences, which suggests that these protein motions are slaved by the α-relaxation. Furthermore, the α-relaxation of the trehalose solution is slower than for the corresponding sucrose solution, and thereby also the protein motions become slower in the trehalose solution, which explains the more efficient stabilizing effect of trehalose on proteins above T g .